The international swimming league - an analysis from a training science perspective - Feser, S.; Hohmann, A.; Behr, J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION This study investigated whether participation in the ISL in 2020 had an impact on swimmers' Olympic preparation and whether participation in the ISL influenced swimmers' performance at the Olympic Games (OS) in Tokyo 2021.